La Conciliación en Muerte Culposa en Accidente de Tránsito Ocasionada por Vehículo Particular, al Amparo de la Mínima Intervención Penal en el Estado Constitucional de Derechos - Castillo Paute, Anahí Stephany (2023)
The present curricular integration work entitled Conciliation in wrongful death in a traffic accident caused by a private vehicle, under the protection of the minimum criminal intervention in the constitutional State of rights" is of interest to develop the investigation because it is a duty fundamental to the Ecuadorian State, constitutionally established, to guarantee a culture of peace, which is reflected in the peaceful settlement of conflicts. The Ecuadorian constitutional State of rights and justice has maintained a traditional form of conflict resolution through formal justice committed to the intervention of the ius puniendi of the State and disinterest in the active participation of the victim and the offender in resolving their conflicts. The Constitution of the Republic of Ecuador recognizes the application of alternative means of conflict resolution, such as arbitration, mediation, and other alternative procedures. The Comprehensive Organic Criminal Code acknowledges the application of reconcilement as an alternative mechanism to conflicts generated by the commission of a crime; however, in terms of traffic offenses, this legal concept is not allowed if the consequence of the infringement is the death of one or more people or serious injuries that cause permanent disability or loss of any organ. Therefore, it was essential to identify the importance of analyzing the possibility of reconciling in the case of the criminal type of death due to negligence typified in article 377 of the Comprehensive Organic Criminal Code; first paragraph, under the protection of the minimum intervention of criminal law that guarantees that the State will intervene in the trial and sentence of a person only when it is strictly necessary, and there is no other alternative; a mechanism that can be found in reconciliation. In the present investigation, materials and methods were applied, which permitted the development of the research. Interviews and surveys were carried out with legal professionals, specifically in the traffic and road safety branch; results served to propose the legal reform project to the Comprehensive Organic Criminal Code, which aims to extend conciliation to cases of death due to negligence in traffic accidents.